Ethics Precedes Religious Beliefs: The Basis of Solidarity (KEMANUSIAAN The Asian Journal of Humanities, 2016)
In this paper, I attempt to engage with the evidentialist principle of William Clifford in conjunction with the normative that the doctrinal and practical correlates of religious beliefs ought not to endorse any serious moral violations. This in turn facilitates the articulation of a structure for the basis of solidarity amongst people of different faiths. With the help of Kant's reflections on the concept of faith and on religion, I argue that ethics ought to have priority over religious beliefs, and this is essential in establishing a foundation for fostering an integrative existence amongst members of a multi-religious polity.